How Much Are Amenities Worth? An Empirical Study on Urban Land and Housing Price Differentials across Chinese Cities - Yan Song; Jiang Zhou; Yingjie Zhang; Dingxin Wu; Honghai Xu (Land, 2022)
As China is transitioning from a planned economy to a market-based economy, over the past 30 years, China’s economy has experienced the same type of changes that led to amenity-driven housing and land markets in more developed countries. This paper examines the effect of different types of amenities on urban land and housing prices across Chinese cities in 2020. When firms and households value some amenities, the assumption is that the preference for these amenities will be valued and reflected in both land and housing markets. We conduct a cross-sectional analysis of urban land and housing prices in prefecture and higher-level cities in China. We extend the Roback model to explore the extent to which the different land rents and housing prices reflect the compensations for interregional amenity differences across Chinese cities. We include two types of amenities: natural amenities and locally produced amenities. We perform two-stage least squares (2SLS) estimations and compute the implicit prices of various amenities for households and firms. The empirical results show that a range of amenities is valued by both households and firms, resulting in higher housing and industrial prices.